(untitled) (Ameghiniana, 2013)
A Cypridea-bearing ostracodal assemblage and the associated charophytes from continental to brackish hauterivían levels of the Agrio Formation, in the Neuquén Basin of the Andean Domain, are described. Eight taxa of Ostracods are recognízed, including Cypridea australis major nov. subsp. and "Comphocuthere" neuquensis alata nov. subsp. anel two of charophytes frorn which Mesochora maruchoensis nov. sp. is proposed.